2003
DOI: 10.1002/aic.690490316
|View full text |Cite
|
Sign up to set email alerts
|

Optimum photolysis in Taylor–Couette flow

Abstract: Photolysis was studied in Taylor ᎐ Couette flow, and a similarity law proposed for the formation of a product from a fast photochemical reaction in the presence of laminar Taylor ®ortices. The concentration of the product formed depended on both the dosage of photons and a reaction-layer thickness, defined by the radiation penetration depth. In particular, for a gi®en flow rate and radiation intensity, the UV photolysis of iodide produced a maximum concentration of the product triiodide, when the radiation pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The first design approach used a thin-film flow for liquid foods, e.g. CiderSure reactor that was developed as a UV light processing equipment in 1998 (FPE Inc., Macedon, NY) (CiderSure, 2010) and the Taylor-Couette flow UV reactor constructed by Pierson in 2003 (Forney &Pierson, 2003). A second design approach focused on increasing of the turbulence within a UV reactor, e.g.…”
Section: Introductionmentioning
confidence: 44%
“…The first design approach used a thin-film flow for liquid foods, e.g. CiderSure reactor that was developed as a UV light processing equipment in 1998 (FPE Inc., Macedon, NY) (CiderSure, 2010) and the Taylor-Couette flow UV reactor constructed by Pierson in 2003 (Forney &Pierson, 2003). A second design approach focused on increasing of the turbulence within a UV reactor, e.g.…”
Section: Introductionmentioning
confidence: 44%
“…Previous studies on the effects of radiation in Taylor−Couette flow are the growth of algae () and the development of a reactor for heterogeneous photocatalysis (). More recently, Forney and Pierson ( , ) considered a fast photolytic reaction and demonstrated that optimum photoefficiencies could be achieved if the radiation penetration depth was equal to the velocity, boundary layer thickness. The latter work also provided a scaling law for the yield in both Taylor−Couette and channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…The group of Forney considered fast photocatalytic reactions, like the oxidation of iodide (I − ) to iodate (I 3 − ) 105 . They developed a law of similarity for the product development incorporating Taylor‐vortices and investigated the optimal operating parameters of the TCR ( Ta , ω ) to maximize photoefficiency, which occurred when the radiation penetration depth equals the boundary‐layer thickness.…”
Section: Application Of the Tcr In Process Technologymentioning
confidence: 99%